Policing and Security in Practice
XXIII, 227 p.
Keywords: This volume addresses critical questions about how to achieve the best outcomes from police and security providers by reviewing and critiquing the scientific literature and identifying best practice guidelines. Chapters cover a range of topical issues, including legitimacy, organised crime, public protests and intelligence and investigations.